please solve this question.......I will make it as brainleast.......
Attachments:
![](https://hi-static.z-dn.net/files/d66/9d8617e5311e4600dc879d3082612023.jpg)
Answers
Answered by
1
Step-by-step explanation:
Given : two Zero is - 2 and 3
Eqⁿ is x²+(a+1)x+b
Here, a = 1, b = a+1 ; c = b
We know that,
Sum of zero => - 2+3 = - b/a
=> 1 = ( - a-1)/1
=> 1 +1 = - a
=> 2 = - a
=> a = - 2
Similarly,
Products of zero => - 2×3 = c/a
=> - 6 = b/1 =b
Hence, a= - 2 and b = - 6
Answered by
5
Answer:
hey mate, here is ur answer hope it helps you
plz mark as brain lies answer plz plz plz plz plz plz plz plz plz plz plz dear I really need
Attachments:
![](https://hi-static.z-dn.net/files/dce/4b7cd9a84a3cae362b233f7b81d355b2.jpg)
Similar questions